Model coastal-taba: Pengembangan kurikulum menggunakan pedagogi berbasis tempat dan etnosains - Selviana Haenkanes Turot; Asep Herry Hernawan (Curricula: Journal of Curriculum Development, 2026)
National education reforms in Indonesia often assume a land-based connectivity and urban sameness that just doesn’t exist in an archipelagic state. This continental bias creates a deep mismatch, where a one-size-fits-all curriculum sidelines the unique lives of students in coastal 3T regions. Most current efforts fail to bridge this gap because they treat coastal schools as just poor versions of city schools, rather than unique centers of biocultural knowledge. This study builds a new, macro-level framework by revitalizing Hilda Taba’s Inductive Model using a Critical Library Research Design. By analyzing 45 academic and policy documents, this study mapped out where national rules clash with local maritime wisdom. The findings show that for education to be truly fair, the usual top-down approach must be flipped. This study proposes the Coastal-Taba Model, a seven-step process that starts with the student’s own maritime world (Islandness) and local science. By using seasonal schedules and place-based learning, this model moves teachers from being passive implementers to becoming true architects of the curriculum. Ultimately, recognizing the periphery as a valid center of knowledge is the key to making science literacy competitive and meaningful for students in a nation of islands.